The competitive advantages in the construction industry: A theoretical approach - Vlad Leontie (CES Working Papers, 2022)
Because the construction industry is widely viewed as the engine that drives economies around the world, understanding how companies achieve their competitive advantages through innovation, the use of information technologies, strategies, business models, or human resources is vital. The current paper aims to identify and categorize the types of competitive advantages that exist, ranging from pure technological advantages such as information storage, coordination, and electronic communication to organizational and management advantages. In terms of methodological approach, performing a quality analysis of the existent literature regarding competitive advantages consists the best tool due to its wide spectrum of gathering the data. The research will be structured in 3 steps, respectively problem formulation, gathering of the data and title, abstract and full-text review. A complex perspective of the competitive advantages can be therefore obtained which can be a valuable asset in helping a construction enterprise in selecting its long-time strategy for becoming more competitive, efficient and sustainable. Through the main findings, innovation, usage of the informational technologies, initial conditions, environment understanding, safety culture or management practices of the human resources can be counted.
Keywords: 330; competitive advantage; construction industry; innovations; sustainability